New diagnostic criteria for common variable immune deficiency (CVID), which may assist with decisions to treat with intravenous or subcutaneous immunoglobulin. (6th October 2013) - Ameratunga, R.; Woon, S.‐T.; Gillis, D.; Koopmans, W.; Steele, R.
Summary Common variable immune deficiency (CVID) is the most frequent symptomatic primary immune deficiency in adults. The standard of care is intravenous immunoglobulin (IVIG) or subcutaneous immunoglobulin (scIG) therapy. The cause of CVID is currently unknown, and there is no universally accepted definition of CVID. This creates problems in determining which patients will benefit from IVIG/scIG treatment. In this paper, we review the difficulties with the commonly used European Society of Immune Deficiencies (ESID) and the Pan American Group for Immune Deficiency (PAGID) definition of CVID. We propose new criteria for the diagnosis of CVID, which are based on recent scientific discoveries. Improved diagnostic precision will assist with treatment decisions including IVIG/scIG replacement. We suggest that asymptomatic patients with mild hypogammaglobulinaemia are termed hypogammaglobulinaemia of uncertain significance (HGUS). These patients require long‐term follow‐up, as some will evolve into CVID.